The hollywood book of extravagance : The totally infamous, mostly disastrous, and always compelling excesses of America's film and TV idols - Parish, James Robert (John Wiley & Sons, 2007)
The book offers a lengthy behind-the-scenes look at the extravagant pleasures and egos of Tinseltown's sublime and famous. Featured celebrities range from geeks to industry moguls, and from yesterday's idols to today's hottest celebrities. The stars are grouped according to their extremes: ego, neuroticism, partying, power, modern life, and romance. From Mae West to Madonna, Greta Garbo to Marilyn Monroe, Marlon Brando, Bela Lugosi to John Belushi, Zsa Zsa Gabor to Paris Hilton, Errol Flynn to Jude Law, and more.